Probing the interaction of catechin and its β-CD inclusion complex with different food models. (February 2019) - Ho, Siyin; Thoo, Yin Yin; Young, David James; Siow, Lee Fong
Abstract: We have previously reported that the antioxidant activity of catechin degraded dramatically in a protein rich matrix compared to a sugar or oil-based matrix, and that this degradation was significantly retarded by β-cyclodextrin (β-CD) encapsulation. In the present study, we have probed the nature of this interaction of catechin and its β-CD inclusion complex with protein, sugar and oil models using fourier-transform infrared spectroscopy (FTIR) and fluorescence spectroscopy. The former technique revealed a shift and increase in the intensity of the protein amide absorption bands upon mixing with catechin that was not observed with β-CD or with the corresponding encapsulated catechin, suggesting hydrogen bonding between this antioxidant and the protein amide groups. Catechin fluorescence was quenched by all three food models in a concentration dependent manner and this relationship was used to calculate binding constants in each matrix, which also revealed a strong interaction between catechin and protein that was reduced by encapsulation with β-CD. These new results help to explain our earlier observation of catechin degradation by protein and have implications for the use of this important antioxidant in food formulations. Highlights: Free catechin degraded dramatically in protein compared to a sugar and oil model. Strong interaction was observed between catechin and protein. Weak interaction was observed between β-CD encapsulated catechin and protein. β-CD encapsulation helps to protect catechin from degradation.